Circuit Learning in Improving Concentration Student Learning in Madrasah - Fathor Rozi; Moh. Yahya (PALAPA, 2023)
This study aims to explain circuit learning in increasing the learning concentration of 5th grade students at MI Mambaul Ulum. The concentration of learning can be one of the reasons for the success of learning in educational institutions. For this reason, it is necessary to pay sufficient attention to efforts to achieve it. This research uses a qualitative approach with a case study type. There were 4 informants in this study, namely the head of the madrasa, two teachers and one student. Data collection techniques using observation and in-depth interviews. Data analysis used is data collection, data reduction, data display, and conclusions. The research results obtained were, (1) apperception, (2) visualization, (3) forming groups and discussions, and (4) presentations. The implication of this research is that student learning outcomes are getting better.